Sustainable Algae Biodiesel Production in Cold Climates - Rudras Baliga; Susan E. Powers (International Journal of Chemical Engineering)
This life cycle assessment aims to determine the most suitable operating conditions for algae biodiesel production in cold climates to minimize energy consumption and environmental impacts. Two hypothetical photobioreactor algae production and biodiesel plants located in Upstate New York (USA) are modeled. The photobioreactor is assumed to be housed within a greenhouse that is located adjacent to a fossil fuel or biomass power plant that can supply waste heat and flue gas containing CO2 as a primary source of carbon. Model results show that the biodiesel areal productivity is high (19 to 25 L of BD/m2/yr). The total life cycle energy consumption was between 15 and 23 MJ/L of algae BD and 20 MJ/L of soy BD. Energy consumption and air emissions for algae biodiesel are substantially lower than soy biodiesel when waste heat was utilized. Algae's most substantial contribution is a significant decrease in the petroleum consumed to make the fuel.